Investigations of Synonym Replacement for Swedish - Robin Keskisärkkä; Arne Jönsson (Northern European Journal of Language Technology)
We present results from an investigation on automatic synonym replacement for Swedish. Three different methods for choosing alternative synonyms were evaluated: (1) based on word frequency, (2) based on word length, and (3) based on level of synonymy. These three strategies were evaluated in terms of standardized readability metrics for Swedish, average word length, proportion of long words, and in relation to the ratio of errors in relation to replacements. The results show an improvement in readability for most strategies, but also show that erroneous substitutions are frequent.